Husband’s Sexual Violence: Protection Rights for Wives in Terms of Islamic and Indonesian State Law - Hayati, Mulida; Ali, Nuraliah (Al-Risalah, 2021)
This paper discusses the right to protect wives from husband's sexual violence, a perspective of Islamic law, the penal code, and the Law of Elimination of Domestic Violence. In recent years, violence to women has increased, while from a legal standpoint, it has not accommodated various problems related to sexual violence. Therefore, this paper reveals how these protections from three different law perspectives, and prove that these problems can be resolve through those laws. Through normative juridical research using grammatical and systematic interpretation methods, it was found that sexual violence in Islamic Law is categorized as a violation of honor which is punishable by ta’zīr. The punishments regarding violations of a person's freedom are in the form of imprisonment and banishment. In the Penal Code: Offense against decency and persecution. In the Domestic Violence Law: legal protection for victims in the form of physical, psychological, sexual violence. There is a correlation between these three different law perspectives, for instance, the equivalent view which perceives violent behavior as despicable behavior is prohibited, and threatens with imprisonment or ta’zīr. This synergy has implications for fulfilling human protection from violence, implementing a sense of security, and ensuring the survival of the community.